Analisis Faktor-Faktor Yang Memengaruhi Produksi Ikan Bandeng Di Kecamatan Ma’rang Kabupaten Pangkep - Marhawati, Marhawati; Ma'ruf, Muhammad Imam (Universitas Negeri Makassar, 2018)
Fishery development in Province of South Sulawesi can be devided into two categories, they are marine culture and fisheries, include wild fishery and aquaculture. One of aquaculture is brackish water pond. There are several kinds of fish that can grow in brackish water pond, such as milkfish. Milkfish is a potential commodity which is not only for consume but also for export to abroad. The aim of this research is to knowing the factors which affects the production of milkfish in fishpond. The basic research which used is Explanatory Research. This research takes place in Ma’rang subdistrict Pangkep District. The population is all fisherman which total there are 804 fishermen. Simple random sampling is used to get 80 fishermen as samples. They are consist 57 fishermen in Talaka Village and 23 fishermen in Pitue Village. Primary data is gathered by doing interview with the fishermen. This research is used Cobb-Douglas function for analysis. The results of this research show variable of area of fish raising place, young milkfish, fertilizer, burden and region dummy are have significant effect toward production of milkfish in brackish water pond, while labour, feed, age and experience have no effect toeard production pf milkfish in brackish water pond.